Analisis Berpikir Kritis dan Kreatif Mahasiswa Baru Ditinjau dari Kecerdasan Dasar dan Beban Kognitif-Afektif - Muhammad Rizaldi; Oktaviana Ainun Ratnawati; Emy Artuti (EQUALS: Jurnal Ilmiah Pendidikan Matematika, 2026)
Critical and creative thinking are essential competencies for first-year mathematics education students. However, many students still struggle to solve non-routine mathematical problems. This study aimed to analyze students’ critical and creative thinking based on general intelligence and cognitive-affective load. A qualitative phenomenological design was used with 4 students selected purposively from 44 participants representing four groups which are high intelligence–high load, high intelligence–low load, low intelligence–high load, and low intelligence–low load. Data were collected through tests, questionnaires, and interviews. Results showed that students with high general intelligence performed better in both critical and creative thinking than those with low general intelligence. In critical thinking, they identified relevant information, analyzed systematically, evaluated solutions, and made proper decisions. In creative thinking, they demonstrated right and innovative problem solution, while students with low cognitive-affective load also showed stronger novelty. In contrast, students with low general intelligence experienced difficulties in both domains. They struggled to analyze problems critically and generate creative solutions. The study concludes that general intelligence is the main basis of critical and creative thinking, while cognitive-affective load affects how optimally that potential is expressed.